Advanced genetic analysis : finding meaning in a genome - Hawley, R Scott (Blackell Science, 2003)
Advanced Genetic Analysis brings a state-of-the-art, exciting new approach to genetic analysis. Focusing on the underlying principles of modern genetic analysis, this book provides the 'how' and 'why' of the essential analytical tools needed. The author's vibrant, accessible style provides an easy guide to difficult genetic concepts, from mutation and gene function to gene mapping and chromosome segregation. Throughout, a balanced range of model organisms and timely examples are used to illustrate the theoretical basics.